2017
DOI: 10.1177/1933719116669055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Acceptability of Low-Dose Mifepristone and Self-Administered Misoprostol for Ultra-Early Medical Abortion: A Randomized Controlled Trial

Abstract: The aim of this study was to investigate the efficacy, safety, and acceptability of low-dose mifepristone combined with self-administered misoprostol for ultra-early medical abortion. A total of 744 women with ultra-early pregnancy (amenorrhea ≤35 days) who fulfilled the inclusion criteria were enrolled in the study. Equal numbers of participants were allocated randomly to the hospital administration and self-administration groups. All participants took 75 mg mifepristone at the initial visit and 400 µg oral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The search strategy identified 174 articles, of which 15 met our inclusion criteria (Tables 1-2) [2,10,[12][13][14][15][16][17][18][19][20][21][22][23]. Seven articles met criteria but did not report data disaggregated by gestational age less than 42 days; corresponding authors were contacted to ask for these data [19,[24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy identified 174 articles, of which 15 met our inclusion criteria (Tables 1-2) [2,10,[12][13][14][15][16][17][18][19][20][21][22][23]. Seven articles met criteria but did not report data disaggregated by gestational age less than 42 days; corresponding authors were contacted to ask for these data [19,[24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Six randomized controlled trials reporting on successful medical abortion at less than 42 days' gestation were identified (Table 1) [10,[12][13][14][15][16]. The quality of the studies ranged from fair to good.…”
Section: Randomized Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that women self-managing first trimester TOP have varied experiences [2][3][4] but are no more likely to re-attend with complications than those treated in hospital. 5 Although a growing body of literature suggests that self-management is acceptable to women, 2,[6][7][8][9][10][11][12][13][14][15][16][17] there is a need to monitor and understand women's needs around this model of provision, to facilitate provision of the best possible support. Our research contributes to this understanding, by examining details of women's experiences of self-management ≤63 days, of which to date, relatively little is known.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous substances with property of uterine contractility include prostaglandins (PGE2 and PGF2a) and their synthetic analogues (gemeprost, sulprostone, meteneprost and misoprostol), cytotoxic drugs as methotrexate, the anti-progesterone mifepristone and aromatic organic compounds as ethacridine lactate [11,12]. It is widely accepted that a remarkable possibility of attaining complete expulsion of conceptus tissue occurs when prostaglandin analogues and mifepristone are used together [13,14]. The introduction of these agents in the maternal healthcare has also brought about a breakthrough to preventing premature mortality and pregnancy related maternal complications [15].…”
Section: Introductionmentioning
confidence: 99%